PKM Literatur Keuangan Dalam Pengenalan Aplikasi Pinjaman Online Terhadap Mahasiswa Universitas - Cornellia, Riri; Oktaviani, Anggi; Handayani, Hapsari (Neolectura, 2024)
The Covid-19 pandemic in 2021 impacted the increasing diversity of basic needs in society and accelerated digitalization, which has now become a lifestyle. Easy access to digital platforms for shopping, education, investment, payments, and loans has made wise financial management essential. According to data from the Financial Services Authority (OJK), the total distribution of online loans from Fintech Lending in Indonesia reached IDR 225.55 trillion in 2022, an increase of 44.6% from the previous year. Fintech simplifies loan access through peer-to-peer (P2P) lending products that are fast and without complicated requirements, attracting the interest of young generations. Therefore, financial literacy is crucial for Sampoerna University students to address the low level of financial understanding amid the proliferation of online loan applications. Knowledge of risk management is needed so that students can make wise and responsible financial decisions and manage their finances effectively.